Out-of-pocket expenditure for hospitalization in Haryana State of India: Extent, determinants & financial risk protection - Sharma, Deepshikha (Indian J Med Res, 2017)
BACKGROUND & OBJECTIVES: India aspires to achieve universal health coverage, which requires ensuring financial risk protection (FRP). This study was done to assess the extent of out-of-pocket (OOP) expenditure and FRP for hospitalization in Haryana State, India. Further, the determinants for FRP were also evaluated. METHODS: Data collected as a part of a household level survey conducted in Haryana ‘Concurrent Evaluation of National Rural Health Mission: Haryana Health Survey’ were analyzed. Descriptive analysis was undertaken to assess socio-demographic characteristics, hospitalization rate, extent and determinants of OOP expenditure and FRP. Prevalence of catastrophic health expenditure (CHE) (more than 40% of non-food expenditure) and impoverishment (Int$ 1.25) were estimated. Multivariate logistic regression was used to assess determinants of FRP. RESULTS: Hospitalization rate was found to be 3106 persons or 3307 episodes per 100,000 population. Median OOP expenditure on hospitalization was ₹ 8000 (USD 133), which was predominantly attributed to medicines (37%). Prevalence of CHE was 25.2 per cent with higher prevalence amongst males [odds ratio (OR)=1.30], those belonging to scheduled caste and scheduled tribes (OR=1.35), poorest 20 per cent households (OR=3.05), having injuries (OR=4.03) and non-communicable diseases (OR=3.13) admitted in a private hospital (OR=2.69) and those who were insured (OR=1.74). There was a 12 per cent relative increase in poverty head count due to OOP payments on healthcare. INTERPRETATION & CONCLUSIONS: Our findings showed that hospitalization resulted in significant OOP expenditure, leading to CHEs and impoverishment of households. Impact of OOP expenditures was inequitably more on the vulnerable groups. OOP expenditure may be curtailed through provision of free medicines and diagnostics and removal of any form of user charges.